SPATIAL ANALYSIS OF MOBILE PHONE APPLICATION USAGE AMONG GOVERNMENT PENSIONERS IN PERLIS - Wan Qurratu Marsha Wan Zulmajdi; Nazirah Md Tarmizi; Noraini Nasirun@Hirun (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Spatial analysis of the use of mobile phone applications among government pensioners in Perlis is the focus of this study. The main objective is to study the extent of the skill level of using mobile phone applications among government pensioners in Perlis, based on the respective parliamentary constituencies of Padang Besar, Kangar and Arau. Data for this study was collected through a well-designed questionnaire that was distributed to respondents at the government pensioners agency in Perlis. By processing the acquired data, a spatial distribution map was created, depicting the geographical spread of the government pensioners respondent in Perlis. This map provides valuable insight into the varying levels of mobile phone app usage among government pensioners in each parliament. Through this analysis, this study shows government pensioners in the Kangar Parliament have a very good level of usage for mobile phone application that is 60% compared to the Arau and Padang Besar Parliaments. The results from the questionnaire analysis reveal five (5) sections that are demographic, awareness on mobile phone application usage, the opinion of government pensioners about mobile phone applications, self-evaluation of government pensioners in the level of mobile phone application usage, and recommendations. This information is useful to plan suitable community activities with government pensioners in order to upgrade their ability with the current technologies on mobile phone application usage.